Comparing Femtosecond Lenticule Extraction (FLEx) and Femtosecond Laser In-situ Keratomileusis (LASIK) for Myopia and Astigmatism - Tina Marie Saban-Roa, MD; Irwin Cua, MD; Ruben Lim Bon Siong, MD (Philippine Journal of Ophthalmology)
Objective: To compare the efficacy, safety, predictability, stability, contrast sensitivity, and higher-order aberration (HOA) of patients who had femtosecond lenticule extraction (FLEx) and femtosecond laser in-situ keratomeleusis (LASIK) for the correction of moderate myopia and astigmatism.